Prenatal Stress as a Modifier of Associations between Phthalate Exposure and Reproductive Development: results from a Multicentre Pregnancy Cohort Study. Issue 2 (17th November 2015) - Barrett, Emily S.; Parlett, Lauren E.; Sathyanarayana, Sheela; Redmon, J. Bruce; Nguyen, Ruby H. N.; Swan, Shanna H.
Abstract: Background: Prenatal phthalate exposure is associated with altered male reproductive tract development, and in particular, shorter anogenital distance (AGD). AGD, a sexually dimorphic index of prenatal androgen exposure, may also be altered by prenatal stress. How these exposures interact to impact AGD is unknown. Here, we examine the extent to which associations between prenatal phthalate exposure and infant AGD are modified by prenatal exposure to stressful life events (SLEs). Methods: Phthalate metabolites [including those of diethylhexyl phthalate (DEHP) and their molar sum (ΣDEHP)] were measured in first trimester urine from 738 pregnant women participating in The Infant Development and the Environment Study (TIDES). Women completed questionnaires on SLEs, and permitted infant AGD measurements at birth. Subjects were classified as 'lower' and 'higher' stress (0 first trimester SLEs vs. 1+).We estimated relationships between phthalate concentrations and AGD (by infant sex and stress group) using adjusted multiple regression interaction models. Results: In the lower stress group, first trimester ΣDEHP was inversely associated with two measures of male AGD: anoscrotal distance (AGD‐AS; β = −1.78; 95% CI −2.97, −0.59) and anopenile distance (AGD‐AP; β = −1.61; 95% CI −3.01, −0.22). By contrast, associations in the higher stress group were mostly positive and non‐significant in male infants. No associations were observed in girls. Conclusions: Associations between prenatal phthalate exposure and altered genital development were only apparent in sons of mothers who reported no SLEs during pregnancy. Prenatal stress and phthalates may interact to shape fetal development in ways that have not been previously explored.